Sofosbuvir in the treatment of early HCV infection in HIV-infected men. Issue 2 (4th March 2017) - El Sayed, Ahmed; Barbati, Zachary R.; Turner, Samuel S.; Foster, Andrew L.; Morey, Tristan; Dieterich, Douglas T.; Fierer, Daniel S.
Abstract : Background : There is an international epidemic of hepatitis C virus (HCV) infection among HIV-infected men who have sex with men. We previously showed that adding telaprevir to pegylated interferon (IFN) and ribavirin (RBV) both shortened treatment and increased the cure rate of early HCV in these men. Whether shortening treatment of early HCV using IFN-free regimens would be similarly successful has not yet been demonstrated. Methods : We performed a pilot study of treatment with sofosbuvir (SOF) + RBV for 12 weeks in early genotype 1 HCV infection in HIV-infected men. The primary endpoint was SVR 12. Results : Twelve men were treated with 12 weeks SOF + RBV and 11 (92%) achieved SVR 12. Most (63%) were actively using recreational drugs, mostly methamphetamine. The one man who failed had laboratory results more characteristic of chronic than of early HCV infection. The overall safety profile was similar to that known for SOF + RBV. Conclusions : The success of this short-duration IFN-free treatment in early HCV infection is proof in principle that enhanced treatment responsiveness is an inherent characteristic of early HCV infection and not a function of IFN treatment itself. Future studies should now be done with more potent regimens to try to further shorten therapy. In the mean time, in clinical practice early HCV infection should be treated immediately after detection to take advantage of short-duration treatments, as well as to decrease further HCV transmission among HIV-infected MSM.